IDENTIFIKASI KEBUTUHAN TEKNIS UNTUK PENINGKATAN LAYANAN âWAROENG SPESIAL SAMBALâ MENGGUNAKAN ERGONOMICS FUNCTION DEPLOYMENT (EFD) - , MELIA WIDYA KARTIKA SARI, Dr. Kuncoro Harto Widodo, STP, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, there have emerged many restaurants offering spicy sauce (sambal) as their main menu. It requires every restaurant including âWaroeng Spesial Sambalâ to pay more attention to customer satisfaction to ensure customer loyalty. Therefore, to obtain customer satisfaction the parties of the restaurant must understand what things considered important and needed by their customers are. This studyâs aims were to know customer needs toward services provided by âWaroeng Special Sambalâ and to design services that are suitable for customer needs, in which customer satisfaction can be achieved from the aspect of ergonomics. This study was a combination of ergonomics and Quality Function Deployment called Ergonomics Function Deployment. In Ergonomics Function Deployment, the attributes of customer needs were based on the aspect of ergonomics, in which then they were analyzed using Quality Function Deployment method to obtain the concept of technical needs that must be implemented. The result of this study were the House of Quality (HoQ) showing important service attributes of customers such as roomâs temperature, the cleanliness of dinning sets (e.g. spoon, glass, and plate), the readiness of employees in handling orders and complaints, the match of bought and ordered menu, and the speed of services from employees. While, the technical need attributes required in service quality development from the aspect of ergonomics were the management of the restaurant has provided a good continuously service technique training for their employees, reward for employeesâ achievement, employeesâ performance evaluation, some special employees to handle cleanliness, and fans and ventilation.